THE EFFECT OF PHYSICAL CONDITIONS OF HOME AND WORK ENVIRONMENT ON THE EVENT OF PULMONARY TUBERCULOSIS IN CONSTRUCTION WORKERS - Ade Maulida Gultom; Nurmaini Nurmaini; Fazidah Aguslina Siregar (Jurnal Riset Kesehatan, 2022)
Tuberculosis (TB) is a directly-infectious disease caused by tuberculosis bacteria (Mycobacterium tuberculosis) that are airborne through droplets or nuclei when a patient coughs and the saliva droplets containing the bacteria are inhaled by another person while breathing. The research investigates the effect of the physical conditions of the house and working environment on the pulmonary TB events among construction workers in the Asahan Regency. It is an analytic epidemiological survey with a case-control design, and involves examining the entire population amounting to 74 people: the first 37 suffered from pulmonary TB and worked as construction workers (case-group), and the other 37 didn't suffer from pulmonary TB and worked as construction workers (control-group). They were analyzed by using univariate analysis, bivariate analysis, and multivariate analysis. The results showed that the types of floor (p=0.040), lighting (p=0.027), wall (p=0.034), working lengths (p=0.102), and masks uses (p=0.000) have affected pulmonary TB events. In this case, the use of masks (p=0.003) was the most dominant variable. This study suggests counseling on healthy houses for families who are prone to pulmonary TB. Good types of lighting, floor, and wall can be useful in every house to reduce the risk of TB developing to last for a long period or leading to death.